Main problems of Far Eastern vegetable growing - N. A. Sakara; A. V. Soldatenko; V. F. Pivovarov; G. I. Sukhomirov; T. S. Tarasova; V. I. Oznobikhin (Овощи России)
For the Russian Far East (RDV), the subjects are calculated self-sufficiency of vegetable products and its connection with the population. A close correlation between these indicators has ignore once. In order to stabilize the population and consolidate it, it is necessary to increase dramatically the production of vegetables. There are a number of prerequisites for this: a network of research agricultural institutions throughout the territory and a specialized 1Primorskaya vegetable experimental station – branch of the Federal scientific vegetable center in the south of the region, has established. Its employees have clarified the basics of Far Eastern vegetable farming (principles of selecting sites for vegetable plantations and pre-intensive cultivation of their soils, reclamation of the territory; experimentally tested and recommended specialized crop rotations, their effective links; refined fertilizer system; system of resource-saving treatment of soils on the basis of crest-ridge cultivation technology), a number of promising varieties of vegetables "borscht" group, established their seed production, solved many issues of mechanization for cultivation processes. Significantly, important areas of further work were planned.